Boarding House Ownership as a Strategy for Women's Economic Liberation from a Radical Feminist Perspective - Ajeng Dewi Rachmawati; Ahmad Ridwan; Muhammad Faruki (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines boarding house (kos-kosan) ownership as a strategy for women's economic liberation from patriarchal structures in Sidoarjo Regency, East Java, Indonesia, analysed through a radical feminist lens. While substantial scholarship addresses women's economic empowerment in Indonesia, no study has specifically theorised boarding house ownership as a site of patriarchal resistance. Using qualitative case study methodology with in-depth semi-structured interviews, participatory observation, and document analysis, three women boarding house owners were studied in October 2025. Data were analysed thematically following Braun and Clarke's (2006) framework, with methodological triangulation and member checking ensuring rigour. Findings reveal that women's motivations transcend financial calculation to encompass aspirations for economic autonomy, identity reconstruction, and psychological liberation. Women navigated structural barriers including gender-biased banking systems, patrilineal inheritance complexities, and discriminatory licensing bureaucracy, alongside cultural barriers rooted in domestic role expectations and social stigma. The multidimensional impact of ownership encompasses stable passive income, transformed social identity from relational to individual, enhanced psychological agency, and renegotiated gender power relations within families. Theoretically, this study contrMrs.tes to radical feminist discourse by demonstrating how productive property ownership functions as embodied resistance against patriarchal dependency structures in a Global South context, extending Walby's (1990) and Kabeer's (1999) frameworks beyond Western settings. Practically, findings inform policy directions in gender-responsive financing, property licensing reform, and women's financial literacy programmes.